The Impact of Neoadjuvant Treatment on Survival in Patients Undergoing Pancreatoduodenectomy With Concomitant Portomesenteric Venous Resection: An International Multicenter Analysis. Issue 5 (4th November 2021) - Machairas, Nikolaos; Raptis, Dimitri A; Velázquez, Patricia Sánchez; Sauvanet, Alain; Rueda de Leon, Alexandra; Oba, Atsushi; Koerkamp, Bas Groot; Lovasik, Brendan; Chan, Carlos; Yeo, Charles J.; Bassi, Claudio; Ferrone, Cristina R.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of this study was to evaluate whether neoadjuvant therapy (NAT) critically influenced microscopically complete resection (R0) rates and long-term outcomes for patients with pancreatic ductal adenocarcinoma who underwent pancreatoduodenectomy (PD) with portomesenteric vein resection (PVR) from a diverse, world-wide group of high-volume centers. Summary of Background Data: Limited size studies suggest that NAT improves R0 rates and overall survival compared to upfront surgery in R/BR-PDAC patients. Methods: This multicenter study analyzed consecutive patients with R/BR-PDAC who underwent PD with PVR in 23 high-volume centers from 2009 to 2018. Results: Data from 1192 patients with PD and PVR were collected and analyzed. The median age was 68 [interquartile range (IQR) 60-73] years and 52% were males. Some 186 (15.6%) and 131 (10.9%) patients received neoadjuvant chemotherapy (NAC) alone and neoadjuvant chemoradiotherapy, respectively. The R0/R1/R2 rates were 57%, 39.3%, and 3.2% in patients who received NAT compared to 46.6%, 49.9%, and 3.5% in patients who did not, respectively ( P =0.004). The 1-, 3-, and 5-year OS in patients receiving NAT was 79%, 41%, and 29%, while for those that did not it was 73%, 29%, and 18%, respectively ( P <0.001). Multivariable analysis showed no administration of NAT, high tumor grade, lymphovascular invasion, R1/R2 resection, no adjuvant chemotherapy, occurrence of Clavien-Dindo grade 3 or higher postoperative complications within 90 days, preoperative diabetes mellitus, male sex and portal vein involvement were negative independent predictive factors for OS. Conclusion: Patients with PDAC of the pancreatic head expected to undergo venous reconstruction should routinely be considered for NAT.